Factors Effecting Delay to Surgery and Length of Stay for Hip Fracture Patients - Ricci, William M. (J Orthop Trauma, 2015)
PURPOSE: The purpose of this study was to determine factors, including day of week of hospital admission, associated with delay to surgery (DTS) and increased length of stay (LOS) in patients with hip fractures. DESIGN: Retrospective SETTING: Level I Trauma Center PATIENTS AND METHODS: Six hundred and thirty five consecutive patients admitted to a single hospital between January 1999 and July 2006 age 65 or older with a hip fracture (OTA 31) were identified retrospectively from an orthopaedic database. Demographic data, ASA score, hospital admission and discharge dates, the date of surgery, and details of any pre-operative cardiac testing were extracted from the hospital record. These data were used to identify the day of week for hospital admission and to calculate days for DTS and hospital LOS. Linear regression was used to identify independent variables associated with DTS and increased LOS. INTERVENTION: All patients underwent surgical treatment of a hip fracture (OTA 31) MAIN OUTCOME MEASURES: Factors effecting DTS and LOS. RESULTS: Independent factors associated with DTS included the day of week for hospital admission, ASA score, and the need for pre-operative cardiac testing. Patients admitted Thursday through Saturday had longer DTS (mean 2.2 to 2.7 days) than did patients admitted other days (mean 1.7 – 1.8). Delay to surgery increased for increasing ASA: 1.4 days for ASA 2; 2.0 days for ASA 3; and 3.0 days for ASA 4. Those requiring pre-operative cardiac testing had an increased number of days to surgery (mean 3.2 days) than those without (1.7 days). Independent factors associated with increasing hospital LOS included ASA, the need for pre-operative cardiac testing, male gender, and day of admission. Length of stay increased for increasing ASA: 6.3 days for ASA 2; 8.1 days for ASA 3; and 10.1 days for ASA 4. Those requiring pre-operative cardiac testing had an increased LOS (mean 9.4 days) than those without (7.3 days). Male patients had a longer LOS (mean 9.8 days) than did females (mean 7.3 days). Patients admitted on Thursday or Friday (mean 8.5 – 9.1 days) had longer LOS than those admitted on other days (mean 7.3 – 7.9 days). CONCLUSIONS: This is the first study to consider and identify day of admission and need for pre-operative cardiac tests as determinants of DTS and LOS for geriatric hip fracture patients. Relative scarcity of weekend hospital resources, when present, may be responsible for these delays. This study also confirms that patient medical condition as measured by ASA affects both DTS and LOS.